Analyzing Political Rhetoric in the 2024 Indonesian Election: A Critical Discourse Analysis Approach And Its Implications for Civic and Media Education - Agus Setyonegoro; Eko Kuntarto; Saharudin Saharudin; Desti Angraini (AL-ISHLAH: Jurnal Pendidikan, 2025)
Political campaign rhetoric offers a rich context for fostering critical media literacy and civic reasoning in higher education. In the wake of Indonesia’s 2024 general election, campaign discourse has permeated digital platforms, shaping public perception and political engagement. This study applies Norman Fairclough’s dialectical-relational Critical Discourse Analysis (CDA) to online campaign materials published between November 2023 and February 2024. The research investigates how rhetorical strategies reflect power dynamics and ideological framing, while also exploring CDA’s applicability as a pedagogical tool in civic and media education. Analysis reveals recurring discursive patterns, including aggressive diction, strategic ambiguity, instrumental truth claims privileging practicality over evidence, and the erosion of empathetic or constructive language. These features often steer public narratives toward polarized, personality-driven debate formats, diminishing deliberative quality and civic trust. Findings underscore the civic implications of political discourse and support the integration of CDA-based tasks—such as metaphor audits, stance tracking, and ethical reframing—into curricula like SKOM4314 (Perencanaan Pesan dan Media). Positioned as both method and pedagogy, CDA enables students to critically engage with language, identify manipulative rhetoric, and produce evidence-based counter-discourse. The study contributes to discourse-analytic and educational scholarship by demonstrating how analysis of political language can directly inform instructional design aimed at strengthening democratic participation.